Reputational, Credit, Operational Risk to Murabahah Margin Income. Quality of Profit: Car, Roe - Sugihyanto, Toto; Murtanto, Murtanto (The Islamic Education and Multiculturalism Foundation, 2024)
The purpose of this study is to determine the effect of reputational risk, credit risk, and operational risk on murabahah margin income with profit quality as a moderation variable in Islamic commercial banks, CAR and ROE as a Control Variable. This research uses secondary data from financial records or annual reports of 15 Sharia Commercial Banks and 20 Sharia Business Units written in the Financial Services Authority for 2011 to 20121. Using the Structural Equation Model based on Partial Least Squares, the research hypothesis was tested. Research findings show that reputation risk hurts murabahah margin income, credit risk has a significant positive effect on budget income, and there is a positive influence on operational risk competence of cheap margin income, there is a strong influence on profit quality in influencing murabahah margin income from reputation risk, there is a strong influence of profit quality in influencing margin income Murabahah from credit risk, there is a strong influence of profit quality in influencing murabahah margin income from operational risk. Implications, for reference materials for Islamic commercial banks in determining policies and performance planning to be achieved that will find related risks. Orsinil, this study presents new empirical findings on murabahah margin income on reputational risk, credit risk, and operational risk of Islamic Commercial Banks in Indonesia